PERLINDUNGAN HUKUM PEKERJA RUMAH TANGGA BERBASIS HAK KONSTITUSIONAL - Fadhli Junaidi (LPPM Universitas Ekasakti, 2020)
This paper discusses the importance of constitutional rights-based legal protection for domestic workers. The lack of attention from the Indonesian Government towards domestic workers has resulted in employers not treating domestic workers in Indonesia well. The main problem in this paper is that there are still many problematic issues that occur in domestic workers. One of them is the minimal wages received by domestic workers which results in the realization of constitutional-based human rights of domestic workers in accordance with Ministerial Regulation No.2 of 2015 concerning the Protection of Domestic Workers. The method used is qualitative research with a descriptive approach. The data collection technique is based on literature study and from online journals. The results of the analysis of this article are the existence of legal protection for domestic workers that has been implemented in Indonesia, such as the 1945 Constitution of the Republic of Indonesia, Law No.13 of 2003 concerning Manpower, the Civil Code, and the PERMENAKER. RI NO.2 of 2015 concerning Legal Protection for Domestic Workers in effect in Indonesia is hoped that there will no longer be overlaps between employers and domestic workers that are not based on constitutional rights.